Calcifications in a clear cell mucoepidermoid carcinoma: a case report with histological and immunohistochemical findings - do Prado, Renata Falchete; Lima, Celina Faig; Rebelo Pontes, Helder Antonio; Almeida, Janete Dias; Guimaraes Cabral, Luiz Antonio; Carvalho, Yasmin Rodarte (Elsevier B.V., 2007)
The aim of this study was to report an unusual case of mucoepidermoid carcinoma (MEC) in a 39-year-old woman. The tumor showed a prominent population of clear and intermediate basal cells. Clear cells rarely predominate over other cell types. Such cases are called clear cell variant of MEC. The case also revealed a variable amount of calcified material in the tumor mass. Calcifications are rare in clear cell MEC. These structures were periodic acid- Schiff positive and diastase resistant, excluding glycogen origin. Immunohistochemistry was performed, and the epidermoid component was positive for cytokeratin (CK) 7, CK13, CK14, and CK19. The mucous and clear cells presented mild staining for CK7. Cytokeratins 7, 13, and 19 stained luminal cells, and intermediate cells exhibited positivity for CK7, CK14, and vimentin. The origin of the calcifications is speculated to be the result of dystrophic calcification of the amorphous eosinophilic material secreted by intermediate basal cells.